The Determination of MSMES Competitiveness Attributes Using the Analytical Hierarchy Process Method - Istianingsih, Nanik; Al Hidayat, Nanang; Maros, Asra'i; H, Hasdani (International Journal of Islamic Business and Management Review, 2022)
Purpose – This study aims to determine the competitiveness attributes of MSMEs in Bungo Regency.. Methodology/approach – By using Analytical Hierarchy Processes (AHP), criteria are determined to be seen to support the competitiveness of MSMEs. Findings - The results are that the criteria for labor productivity are the most important criteria to be improved because the nature of MSMEs in Bungo Regency is still classified as labor-intensive, so the industry needs to provide training to employees to become skilled and productive. Practical implications: The AHP method is able to prove that the criteria set can be a guide for the industry in decision making Social implications: The results of this study can be applied to the industry in decision making so that it becomes right on target and has an impact on improving the performance of the industry in general. Novelty/value – This research is different from the previous research because the criteria used are to find solutions in determining the priority of MSME competitiveness.